Demographic Inclination on Store Image among Shoppers: A Study with Reference to Malls in Kochi - D. Praveen Raj, Gemini. V. Joyand Hari Sundar. G. Ram
This study in albeit is aimed to measure the demographic inclination towards the store image of shoppers while visiting mall based specialty stores. The study carried out at a most popular mall in Kerala, Lulu Shopping Mall, which was recently opened in Kerala. The study yielded rich research results. Most notably, a significant relationship has been found between demographic characteristics viz. gender, age group, education, occupation and household income of respondents and inclination towards store image. Further, results depict a high degree of demographic inclination towards store image among respondents. A good store image lures customers to make a purchase and impulse purchase too, spend more time & money in the store, revisit the store and also maintain customer interest, increase frequency to visit the store, motivate customers to spread positive word of mouth. Therefore, a store needs to be simple to navigate; it must appeal to shopper's sensory perceptions and must create a sense of belonging, a sense of relationship, a sense of security or assurance and a sense of pleasure in the shopping experience in order to flourish, thrive, and germinate by laps & bounce in the Indian retail market.